Development of critical thinking in drawing lessons - Morkytė, J. (Psichologija, 1963)
Systematic perception of reality and development of the very action of drawing facilitate the critical view and evaluation of own drawings. An ability to compare a picture to the reality cultivates further perception of the reality and fosters drawing skills. Therefore, in comprehensive schools, to improve drawing as a creative action to express own thoughts, it is necessary to teach children to see own and classmates’ pictures, feel the relation of the picture and the represented object.Perception of pictures is cultivated by special systematic training. Based on natural attraction of children to compare pictures to reality, it is necessary to train a child to achieve firstly general and later professional and individual semblance, as well as conscious expression of the essence of an object.Initially, the analyzed perception and images preserved in mind are systematized in an imaginary drawing. To achieve this, a concrete purpose is necessary, clarification of the consistency of the whole drawing, technical instructions. In organizing experience, the main role in primary grades is played by a teacher. S/he may show and finish a concrete drawing, especially when drawing from nature; it is advisable that children themselves can express verbally or mentally their prospective pictures.It is necessary to strive that the form and individual semblance of the drawing is not obscured by superficial and easily achieved finding of similar details. Children must make sure that a picture with many details is not a good one. Only by conscious understanding which details are essential and by accordingly highlighting them, a child will learn to convey the reality things and understand the relation of own picture and the thing.Seeing the picture in a new perspective, as if by the eyes of a spectator, is easier by making breaks, looking from far, in a mirror. Great role is played by mistake correction, analysis of drawings of the class students, assessment of pictures. Perception of pictures is educated by organizing small exhibitions, album compilation, systemized attending to art exhibitions.Cultivated critical assessment of own and other children’s pictures deepen emotional experiences of children and increase their creative potential.
Keywords: teaching art; drawing; critical perception; cultivation of critical perception